Construction and Implementation of English Translation Simulation Training Classroom Based on Deep Learning - Karthikeyan J.; Vasanthan R.; Sundari P.S.; Chong S.T.; Nandhini T.J.; Devi V.C. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper investigates the present situation of translation teaching, counts the survey results, analyzes the results before and after the implementation of the new translation teaching mode, and compares the results between the implemented class and the non-implemented class. Conclusion The translation teaching mode based on flipped classroom is feasible and can be accepted and recognized by students. At the same time, it can arouse students' learning enthusiasm and effectively improve students' translation ability. Translation ability, which reflects the sum of various knowledge and skills that translators need to master to complete translation tasks, is the main goal of translation teaching for professional English. According to the current situation of translation teaching, design the reform scheme of translation practice teaching. The online classroom Blackboard platform is used to implement the flipped classroom teaching mode, and through the reform of diversified teaching contents, process collaborative learning mode, and extracurricular practice expansion, the traditional result teaching of translation is changed into process teaching, so as to improve students' translation cognitive ability, language ability and communicative ability, with a view to providing a new method and perspective for the reform of translation courses for English majors. By using the method of literature research, this paper analyzes the research status of English flip classroom teaching model in domestic colleges and universities. The results show that the purpose of creation is diversified, the types of creation are diversified, the theoretical basis is diversified, the operation process is serialized, and the verification method is integrated. The existing problems mainly include: less capacity development model creation, westernization of theoretical basis, weak problem awareness, unbalanced application, etc. In the future, the research should strengthen the creation of the ability development model, the theoretical basis for the creation should be localized, and the innovative research on the flipped classroom teaching model for English majors should be strengthened. 2023 IEEE.